Evaluadores de este número - Tonon, Graciela (Journal de Ciencias Sociales, 2014)
Dra. Graciela Cruz Jiménez, Universidad Autónoma del estado de México Dra. Beatriz Arita Watanabe, Universidad de Sinaloa, México. Mag. Norma del Rio, Universidad Autónoma Metropolitana-Xochimilco, México. Dr. Alejandro Acosta Ayerbe, CINDE, Colombia. Dr. Norberto Méndez, Universidad de Buenos Aires. Dr. José Burucua Universidad Nacional de San Martín. Dr. Mariano Bartolomé, Universidad de Belgrano. Mag. Marcelo Montes, Universidad Nacional de Villa María.